Design and fabrication of a robotic arm for material handling / P. Nageswara Rao ... [et al.] - Rao, P. Nageswara; Ahmad, Anuar; Omar, Abdul Rahman; Ayub, Muhammad Azmi (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2001)
The commercial robots are expensive for use in the educational institutions. Further the operation of them will not leave room for experimentation which is necessary in an educational institution. Further a large number of components that can be used for building a robot are readily available in the market. Hence this project has been taken up to allow us to build a working robot using as many of the off the shelf components to provide he necessary flexibility. This would make it a low cost robot with enough flexibility for the students to experiment the various functions of the robot. The mechanical component of the manipulator is built with three axes, one rotary and two linear. This configuration is most common to be used as a material handling device for machine tools. The rotary axis is achieved by making use of a pneumatic rotary table and one linear axis is by means of a pneumatic cylinder. The second linear axis in the Z-direction is achieved by the use of an AC servomotor with a ball screw and linear motion elements to provide for accurate positioning capability. The gripper has been designed for cylindrical components, since this robot is conceived as a material handling unit for a CNC turning centre. All the necessary design calculations have been done and the finite element analysis was carried out for the main structure. The control of the robot is one of the crucial elements. A PC is used as a controller. The motion control is carried with the help of a motion control card DC2-PC100. This has the ability to control 2 servo and 2 stepper motors in addition to other digital and analogue controls. The control program is developed with the necessary functioning.